2014
DOI: 10.1371/journal.pone.0084789
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of the Emerging Human Pathogens Trichosporon asahii and Trichosporon asteroides from Other Pathogenic Yeasts and Moulds by Using Species-Specific Monoclonal Antibodies

Abstract: The fungal genus Trichosporon contains emerging opportunistic pathogens of humans, and is the third most commonly isolated non-candidal yeast from humans. Trichosporon asahii and T. asteroides are the most important species causing disseminated disease in immunocompromised patients, while inhalation of T. asahii spores is the most important cause of summer-type hypersensitivity pneumonitis in healthy individuals. Trichosporonosis is misdiagnosed as candidiasis or cryptococcosis due to a lack of awareness and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 26 publications
1
15
0
Order By: Relevance
“…7 It has been suggested that Trichosporon has thinner hyphae and pseudohyphae as compared with Candida, and stains less prominently on GMS as compared with other fungi, but histopathological identification without the benefit of supplemental immunohistochemistry, enzyme-linked immunosorbent assay (ELISA), and/or polymerase chain reaction (PCR) analysis is difficult. [15][16][17] While the patients' skin findings conformed to classical descriptions of T. asahii infection, his biopsy with its dense, neutrophilic peri-eccrine infiltrate more closely resembled NEH on preliminary inspection, an elusive entity observed most commonly in the context of chemotherapy for hematologic malignancy that is histologically characterized by the neutrophilic infiltration of eccrine gland acini with or without acinal necrosis. 18,19 Infectious forms of NEH (better known as infectious eccrine hidradenitis, or IEH) have been described in the literature in the setting of HIV, Staphylococcus aureus, Streptococcus spp., Serratia marcescens, Nocardia spp., Mycobacterium chelonae, and Enterobacter cloacae but never in the context of Trichosporon.…”
Section: Discussionsupporting
confidence: 57%
“…7 It has been suggested that Trichosporon has thinner hyphae and pseudohyphae as compared with Candida, and stains less prominently on GMS as compared with other fungi, but histopathological identification without the benefit of supplemental immunohistochemistry, enzyme-linked immunosorbent assay (ELISA), and/or polymerase chain reaction (PCR) analysis is difficult. [15][16][17] While the patients' skin findings conformed to classical descriptions of T. asahii infection, his biopsy with its dense, neutrophilic peri-eccrine infiltrate more closely resembled NEH on preliminary inspection, an elusive entity observed most commonly in the context of chemotherapy for hematologic malignancy that is histologically characterized by the neutrophilic infiltration of eccrine gland acini with or without acinal necrosis. 18,19 Infectious forms of NEH (better known as infectious eccrine hidradenitis, or IEH) have been described in the literature in the setting of HIV, Staphylococcus aureus, Streptococcus spp., Serratia marcescens, Nocardia spp., Mycobacterium chelonae, and Enterobacter cloacae but never in the context of Trichosporon.…”
Section: Discussionsupporting
confidence: 57%
“…kudriavzevii (anamorph Ca. krusei) (Hautala et al, 2007;Miceli et al, 2011;Davies and Thornton, 2014).…”
Section: Detection Of S Prolificans In Estuarine Muds and Identificamentioning
confidence: 99%
“…This is the first time, to our knowledge, that a mAb‐based detection method has been used to track Fusarium in environmental samples. The mAb was able to differentiate Fusarium from a wide spectrum of unrelated fungi, including the human pathogens Aspergillus (Thornton and Wills, ), Candida , Geotrichum , Rhodotorula and Trichosporon (Miceli et al ., ; Davies and Thornton, ), Cyphellophora and Phialophora (Feng et al ., ), Exophiala (Zeng et al ., ), Trichoderma (Sandoval‐Denis et al ., ), Engyodontium (MacĂȘdo et al ., ; Thamke et al ., ) and Mucor (Petrikkos et al ., ), several of which have been reported previously to inhabit biofilms in water distribution systems (Dogget, ). The 100% accuracy of the ED7 ELISA, confirmed by using ITS sequencing and TEF PCR analysis of recovered isolates, demonstrates its robustness in detecting potentially infectious Fusarium species in polymicrobial communities.…”
Section: Discussionmentioning
confidence: 99%
“…Identification of environmental reservoirs of human pathogenic molds including Fusarium has typically relied on nucleic acid‐based technologies following recovery of fungi using selective media (Anaissie et al ., ; Mehl and Epstein, ; Short et al ., ; Anaissie et al ., ; Rougeron et al ., ). Recently, highly specific monoclonal antibodies (mAb) have been used to identify pathogenic species or species complexes in environmental samples containing mixed populations of yeasts and molds (Thornton, ; Davies and Thornton, ; Thornton et al ., ). While mAb‐based approaches similarly rely on culture for recovery of fungi from environmental samples, detection of diagnostic antigens in crude culture extracts using genus‐ or species‐specific mAbs offers an attractive alternative approach to pathogen detection, particularly when combined with unsophisticated diagnostic modalities such as lateral‐flow technology (Thornton, ).…”
Section: Introductionmentioning
confidence: 99%